Federated Learning: Advancing Privacy-Preserving Machine Learning at Scale - Shreya Gupta (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Federated Learning emerges as a transformative paradigm in machine learning, revolutionizing data privacy and distributed computing across multiple sectors. This comprehensive exploration details the evolution of federated learning from its foundational concepts to practical implementations across healthcare, finance, and industrial applications. The implementation demonstrates remarkable capabilities in preserving privacy while maintaining computational efficiency through various mechanisms, including differential privacy, secure aggregation, and homomorphic encryption. In healthcare scenarios, federated learning has enabled collaborative research across medical institutions while safeguarding patient data privacy. The financial sector benefits from enhanced fraud detection capabilities while maintaining regulatory compliance. The automotive industry utilizes federated learning to improve autonomous driving systems through distributed learning from connected vehicles. Integrating cloud computing and edge processing further enhances system efficiency and scalability. The amalgamation of these technologies presents promising directions for future developments in privacy-preserving distributed computing and machine learning applications.